Benjamin Gerig papers - Gerig, Benjamin, 1894-1976.
Correspondence, memoranda, reports, printed matter, and other papers pertaining to Gerig's service with the League of Nations, 1930-1940, chiefly as commissioner-general of the pavilion at the New York World's Fair (1939-1940); his work with the U.S. Dept. of State in a number of positions involving international organizations and the administration of trust territories, 1942-1961; and his membership on the United Nations Trusteeship Council, 1947-1953. Documents Gerig's participation in the Dumbarton Oaks Conference, 1944; the United Nations Conference on International Organization in San Francisco, Calif., 1945; the Preparatory Commission of the United Nations, 1946; the first session of the U.N. General Assembly, 1946; and the United Nations Visiting Mission to Trust Territories in West Africa, 1958. Subjects include colonialism and colonial policy primarily in Africa, the mandate system, nuclear testing in trust territories, race relations, and the growth of Soviet colonialism.
Correspondents include Isaiah Bowman, Ralph J. Bunche, Andrew W. Cordier, John Foster Dulles, J.W.T. van Erp, Noel Haviland Field, Alger Hiss, Philip C. Jessup, Sean Lester, Henry Cabot Lodge, Paul Manship, Felix M. Morley, Bertram Pickard, Arthur Sweetser, Ruth Gregory Sweetser, John D. Tomlinson, F.P. Walters, Gerig's first wife, Mary Gerig, and his second wife, Pearl Gerig.
Library of Congress Prints and Photographs Division.
Diplomat. Full name: Orie Benjamin Gerig.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bowman, Isaiah, -- 1878-1950 -- Correspondence; Bunche, Ralph J. -- 1904-1971 -- Correspondence; Cordier, Andrew W. -- 1901- -- Correspondence; Dulles, John Foster, -- 1888-1959 -- Correspondence; Erp, J. W. T. van -- Correspondence; Field, Noel Haviland, -- 1904-1970 -- Correspondence; Gerig, Mary, -- 1898-1960 -- Correspondence; Gerig, Pearl -- Correspondence; Hiss, Alger -- Correspondence; Jessup, Philip C. -- 1897-1986 -- Correspondence; Lester, Sean, -- 1888-1959 -- Correspondence; Lodge, Henry Cabot, -- 1902-1985 -- Correspondence; Manship, Paul, -- 1885-1966 -- Correspondence; Morley, Felix M. -- 1894-1982 -- Correspondence; Pickard, Bertram, -- 1892-1973 -- Correspondence; Sweetser, Arthur, -- 1888-1968 -- Correspondence; Sweetser, Ruth Gregory -- Correspondence; Tomlinson, John D. -- 1903-1981 -- Correspondence; Walters, F. P. -- 1888- -- Correspondence; United States. -- Department of State; League of Nations; Preparatory Commission of the United Nations; United Nations; United Nations. -- Trusteeship Council; United Nations Visiting Mission to Trust Territories in West Africa; Colonies; Colonies -- Africa; International agencies; International organization; International trusteeships; International trusteeships -- Africa, West; Mandates; Nuclear weapons -- Testing; Race relations; Soviet Union -- Colonies; Diplomats